10 questions for the Dalai Lama : [videorecording (DVD)] : one man's journey through the northern Himalayas - Ray, Rick; Bstan- dzin-rgya-mtsho, Dalai Lama XIV, 1935- (Monterey Video, 2007)
Ten questions are posed to His Holiness the Dalai Lama by filmmaker and explorer Rick Ray. Ray examines some of the fundamental questions of our time by weaving together observations from his own journeys throughout India and the Middle East, and the wisdom of an extraordinary spiritual leader.